2016
DOI: 10.1016/j.rpto.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Social identity and engagement: An exploratory study at university

Abstract: a b s t r a c tWithin the framework of research on students' active performance in their study habits, the aim of this study is to analyze a model predicting the effect of social identity and personal initiative on engagement in university students. We conducted a cross-sectional study on 266 students from different Spanish universities. The resulting data were analyzed using SPSS Macro MEDIATE. Evidence was found for the proposed model. Only group-identity predicted personal initiative and engagement. Analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
6
0
2
Order By: Relevance
“…In addition, a longitudinal study would allow us to analyze those possible spirals between initiative and work engagement that have been found by [ 12 ], in which work engagement enhances personal initiative and impacts work engagement but not at the group level, spirals that seem very likely due to the inconsistency in previous studies, which sometimes place work engagement as an antecedent and at other times as a consequence or modulator/mediator variable [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a longitudinal study would allow us to analyze those possible spirals between initiative and work engagement that have been found by [ 12 ], in which work engagement enhances personal initiative and impacts work engagement but not at the group level, spirals that seem very likely due to the inconsistency in previous studies, which sometimes place work engagement as an antecedent and at other times as a consequence or modulator/mediator variable [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of work engagement and personal initiative have been studied in separate studies by authors who have minimal contact with one another. At least three different studies have shown positive relationships between work engagement and personal initiative [ 12 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social identity theory indicates that individuals hope to gain social identity and improve self-esteem by maintaining positive recognition from social groups [73]. Social factors of mobile health care refer to a social group's degree of recognition of users' adoption of mobile health care.…”
Section: Environmental Dimension (D 3 )mentioning
confidence: 99%
“…(3) Environmental dimension Social identity theory indicates that individuals hope to gain social identity and improve self-esteem by maintaining positive recognition from social groups [68]. Social regulation is a form of social impact.…”
Section: Analysis Of the Characteristics And Adoption Of Mobile Healtmentioning
confidence: 99%